An approach to packaging waste reverse logistics: case of Slovenia - Lisec, Andrej; Antić, Slobodan; Campuzano-Bolarín, Francisco; Pejić, Vaska (Transport, 2018)
Deriving from insights gained in a concrete empirical quantitative modelling research, the aim of the paper is to present the methodology and results of a Packaging Waste (PW) logistics exploratory study that was conducted in cooperation with a leading southeastern European retail chain company. PW Reverse Logistics (RL) is specific, but an integral part of retail operations and can also represent significant logistics and transportation costs concerns. In our research, we have, with a simulation model, been able to reduce the number of tonne-kilometres for 55% which represents significant cost reduction. The study scope focuses on the RL of industrial PW as the handling object of interest in retail, decoupled from the possible returns flow of non-food items and waste generated on premise by shoppers and employees, classified as non-industrial. It introduces an analytical framework, which has been tested and applied to a real case problem. First Published Online: 25 May 2017